Dysphagia and malignancy: A three‐year follow‐up and survey of National Cancer Registry data. (21st December 2015) - Nevalainen, Pia; Geneid, Ahmed; Ilmarinen, Taru; Pietarinen, Petra; Kinnari, Teemu J.; Rihkanen, Heikki; Ruohoalho, Johanna; Markkanen‐Leppänen, Mari; Bäck, Leif; Arkkila, Perttu; Aaltonen, Leena‐Maija
Abstract : Objectives/Hypothesis: Dysphagia may cause concern about malignancy. Symptoms are often unspecific; thus, it is essential to identify those requiring further investigations. Study Design: Retrospective study combined with patient survey. Methods: Case records of the 303 dysphagia patients referred in 2009 to Helsinki University Hospital, Department of Otorhinolaryngology–Head and Neck Surgery were surveyed. Based on clinical data, the main cause of symptoms divided patients into five groups. Alarming signs were food sticking in the throat or in the esophagus, weight loss, and progressive dysphagia symptoms. A questionnaire sent 3 years after the primary visit concerned the present symptoms. To investigate whether dysphagia could have been early symptom of malignancy, we surveyed the Finnish Cancer Registry database until the end of 2012. Results: Most diagnoses remained descriptive: unspecific dysphagia (167, 55%). Five (0.02%) had malignant disease, for all of whom the suspicion of malignancy was evident. Finnish Cancer Registry data indicated that unspecific dysphagia did not develop into malignancy during a 3‐year follow‐up. Returned questionnaires numbered 154 (62%), of which 30 (19%) were asymptomatic patients; relieved symptoms in 36 (23%), fluctuating or unchanged symptoms in 43 (28%), and worse symptoms in 12 (8%). The remaining patients (33, 21%) had not answered that question or the answer was uninterpretable. Conclusion: Further investigations to reveal malignancy seemed unnecessary if alarming clinical signs or findings were lacking. After 3 years, almost half the patients were asymptomatic or had milder symptoms revealing the condition's potential for spontaneous recovery. Level of Evidence: N/A. Laryngoscope, 126:2073–2078, 2016